THE IMPACT OF USING E-BOOK AND P-BOOK IN STUDENTS’ READING ACHIEVEMENT - Dahlia; Ummi Khaerati Syam; Junaid (FKIP Unismuh Makassar, 2021)
This research aimed at finding out the significant different impact between using e-book and p-book in students’ reading achievement at the third grade of MTSN 4 Jeneponto. The researcher used a quasi-experimental research with two group pretest-posttest which was carried out online during the covid-19 pandemic. The sample was class IX A and IX 18 students. The instrument of this research was reading test. The result of the research showed that the value of t-test in terms of accuracy was 3,509. It was higher than the t-table namely 2, 11991 at the level of significant (p) = 0, 05 with degree of freedom (df) = 16. The differences between t-test and t-table value was very significant. It means that the Null Hypothesis (H0) was rejected and Alternative Hypothesis (H1) was accepted. Therefore, it can be concluded that using P-book is giving more positive impact than using E-book in students’ reading achievement at MTSN 4 Jeneponto.